Analisa Tarikan Pergerakan Pengunjung Wisata Permandian Waterpark Matua Kecamatan Alla Kabupaten Enrekang - Siti Nurain; Hamka Hamka; Imam Fadly; Adnan Adnan (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Waterpark Matua is one of the land use objectives that can generate development attraction as a water recreation destination that offers the potential attraction of a beautiful natural panorama because it offers a view consisting of plantations and rocky hills surrounding the tourist area so that it has a beautiful and exotic photo spot. This study aims to determine the characteristics of visitors, what factors affect the attractiveness of visitors, and the growth rate factor of future visitor attraction using the furness method. This research was conducted for 2 months with questionnaire data collection, and processed using the SPSS 24 application. The results showed that the characteristics of visitors according to gender showed that most visitors were female based on a percentage of 66%, age 11-20 years with a percentage of 38%, most visitors from the Alla, Anggeraja, Curio districts with a percentage level of 38%, Students with a percentage level of 47%, the most visitors' transportation mode is motorbike with a percentage level of 70% and the movement attraction model with multiple linear regression analysis method is Y = 2.839 + 0.340 (x1) - 0.473 (x2) + 0.196 (x3) - 0.228 (x5) + 0.190 (x9) + 0.419 (x12). Factors that influence the occurrence of attraction are variables of home distance (x1), transport costs (x2), length of travel time (x3), destination to tourist attractions (x5), food prices (x9), and building conditions (x12). The growth rate factor from the analysis results using the Furness method obtained a growth factor value of Ed = 0.9897 which has met the requirements of the error tolerance limit, with an expected visitor attraction value of Dd = 3214.